2008
DOI: 10.1029/2006jb004679
|View full text |Cite
|
Sign up to set email alerts
|

Paleoearthquakes of the Düzce fault (North Anatolian Fault Zone): Insights for large surface faulting earthquake recurrence

Abstract: The 12 November 1999 Mw 7.1 earthquake ruptured the Düzce segment of the North Anatolian Fault Zone and produced a ∼40‐km‐long surface rupture. To improve knowledge about earthquake recurrence on this fault, we undertook paleoseismological trench investigations. We found evidence for repeated surface faulting paleoearthquakes predating the 1999 event during the past millennium. Dating was based on radiocarbon, 210Pb analyses, and archaeological considerations. In addition to the 1999 earthquake, prior surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 29 publications
5
36
0
Order By: Relevance
“…[61] Four studies, involving multiple trench sites have been conducted in relatively close proximity on the Düzce Fault that ruptured in the 1999 Düzce earthquake [Hitchcock et al, 2003;Komut, 2005;Pantosti et al, 2008;Pucci, 2006;Sugai et al, 2001]. Sugai et al [2001] used a novel technique involving a geosclicer to constrain earthquake timing near Lake Efteni.…”
Section: Appendix B: Review Of Published Paleoseismic Investigationsmentioning
confidence: 99%
See 2 more Smart Citations
“…[61] Four studies, involving multiple trench sites have been conducted in relatively close proximity on the Düzce Fault that ruptured in the 1999 Düzce earthquake [Hitchcock et al, 2003;Komut, 2005;Pantosti et al, 2008;Pucci, 2006;Sugai et al, 2001]. Sugai et al [2001] used a novel technique involving a geosclicer to constrain earthquake timing near Lake Efteni.…”
Section: Appendix B: Review Of Published Paleoseismic Investigationsmentioning
confidence: 99%
“…We generally disagree with these interpretations and do not use data from this study from further discussion. Because the other studies on the Düzce Fault [Hitchcock et al, 2003;Pantosti et al, 2008] comprise multiple trenches, at locations which overlap one another, Table S3 shows the data from each trench individually. We are unsure whether all of the dates are conventional radiocarbon ages; some are rounded while others are not.…”
Section: Appendix B: Review Of Published Paleoseismic Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge of past earthquakes in earthquake-prone areas raises the possibility of protecting humans and infrastructure (Atakan, et al, 2002;Sørensen et al, 2006). It was for these reasons that the European Union project on "Large Earthquake Faulting and Implications for the Seismic Hazard Assessment in Europe" (RELIEF) was initiated (Pantosti et al, 2008).…”
Section: Movements Of the Anatolian And The Eurasian Plates Along Thementioning
confidence: 99%
“…In our opinion, this is true only in theory. Worldwide practice (e.g., see Ellsworth et al 1999 for California; Shimazaki 2006 for Japan; Pantosti et al 2008 for Turkey) derives α values from observed sets of interoccurrence times, which are affected by epistemic errors due, at least, to completeness and sensitivity reasons (possible missed events and uncertainties in paleoseismic event dates). The aperiodicity α associated to a fault, or to a group of characteristic earthquake sources, should be, therefore, considered a representative of both the aleatory and epistemic variability.…”
Section: Probabilistic Modelmentioning
confidence: 99%